Feasibility and acceptability of early infant screening for sickle cell disease in Lagos, Nigeria—A pilot study - Oluwole, Esther O. (PLoS One, 2020)
In Nigeria, about 150000 babies are born annually with sickle cell disease (SCD), and this figure has been estimated to increase by 100% by the year 2050 without effective and sustainable control strategies. Despite the high prevalence, newborn screening for SCD which allows for early prophylactic treatment, education of parents/guardians and comprehensive management is not yet available. This study explored a strategy for screening in early infancy during the first and second immunization visits, determined the prevalence, feasibility and acceptability of early infant screening for SCD and the evaluation of the HemoTypeSC diagnostic test as compared to the high-performance liquid chromatography (HPLC) gold standard. A cross-sectional study was conducted in two selected primary health care centres in Somolu local government area (LGA) in Lagos, Nigeria. Two hundred and ninety-one mother-infant pairs who presented for the first or second immunization visit were consecutively enrolled in the study following written informed consent. The haemoglobin genotype of mother-infant pairs was determined using the HemoTypeSC rapid test kit. Confirmation of the infants’ Hb genotype was done with HPLC. Data were analysed with SPSS version 22. Validity and Predictive value of HemotypeSC rapid screening test were also calculated. Infant screening for SCD was acceptable to 86% of mothers presenting to the immunization clinics. The prevalence of SCD among the infant cohort was 0.8%. The infants diagnosed with SCD were immediately enrolled in the paediatric SCD clinic for disease-specific care. The HemoTypeSC test had 100% sensitivity and specificity for sickle cell disease in early infancy compared to HPLC. This study affirms that it is feasible and acceptable for mothers to implement a SCD screening intervention program in early infancy in Lagos State. The study also demonstrates the utility of the HemotypeSC rapid testing for ease and reduced cost of screening infants for SCD.